Employer and employee perspectives of HRM practices within SMEs. Issue 3 (2nd September 2021) - Mazzarol, Tim; Soutar, Geoffrey N.; McKeown, Tui; Reboud, Sophie; Adapa, Sujana; Rice, John; Clark, Delwyn
ABSTRACT: This paper examines the perspectives of employers and employees within nano, micro, small, medium, and large firms in relation to HRM practices. The study draws upon a large sample of respondents from firms of all size categories. An online questionnaire comprising established HRM measures was used to collect the data. A multivariate discriminant analysis procedure was used to identify the interrelationships between the employer and employee groups, across firms by size, and how they viewed the importance of the HRM measures. The study found a strong congruence between employers and employees across most constructs and provides insights into the role firm size plays in the formalization of HRM practices and the relative importance of such factors within SMEs.